ANALISIS PENGARUH PEMBIAYAAN USAHA RAKYAT TERHADAP PENGEMBANGAN UMKM DI KOTA BATUSANGKAR (STUDI KASUS UPS. PEGADAIAN SYARIAH) - Sherin Afrila Putri; Cahya Agung Mulyana (Jurnal Ekonomi dan Bisnis, 2025)
This thesis is entitled "Analysis of the Influence of People's Business Financing on the Development of Micro, Small and Medium Enterprises in Batusangkar City (Case Study of UPS Pegadaian Syariah)". Compiled by Sherin Afrila Putri NIM 3320169 Sharia Banking Study Program, State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi. The purpose of this study is to determine how much influence People's Business Financing has on the Development of Micro, Small and Medium Enterprises. The type of research used is quantitative descriptive research. The data used is primary data, with a population of people's business financing in Batusangkar which uses data collection techniques with questionnaires and documentation. Data processing techniques use research instrument tests consisting of validity tests and reliability tests, classical assumption tests consisting of (normality tests, linearity tests), simple linear regression tests, hypothesis tests (t tests), coefficient of determination tests. The results of the study indicate that partially the people's business financing variable has an effect on the development of MSMEs with a significant value of 0.000 ≤0.05 for people's business financing simultaneously there is an influence of the business financing variable people on the development of MSMEs with a significant value of 0.000 ≤0.05, which means that there is an influence of people's business financing on the development of MSMEs. The large result of the determination coefficient test (R2) is 0.754, around 75.4% of the variables used, the remaining 24.6% is explained by other variables outside the regression model analyzed.